2007
DOI: 10.1177/0890334407307547
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human Milk Donors

Abstract: The primary objective of this research was to create a detailed characterization of human milk donors, including descriptive information about demographics and lifestyle, involvement with the milk bank, reasons for donating, problems encountered while breastfeeding and pumping milk, barriers to donating milk, affective experiences, and personal values. Data were collected via telephone interview of 87 donors and 19 nondonor controls. Few relationships were found between the descriptive information and amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 15 publications
5
39
0
4
Order By: Relevance
“…Additionally, the research suggests that several motivations to donate are likely unique to the context of donations to nonprofit milk banks. For example, motivations to donate include having a surplus of milk and wanting to avoid waste (e.g., Azema and Callahan, 2003;Osbaldiston and Mingle, 2007;O'Sullivan, Geraghty, and Rasmussen, 2016); anticipating reciprocity from others, in case the donor comes across the need in the future; a strong belief that human milk is the best nutrition option for babies; and feeling empathy and the desire to ease other babies' and mothers' suffering (Doshmangir, Naghshi, and Khabiri, 2019;Pimenteira Thomaz et al, 2008). Mothers' altruistic motivations are expressed in their desire to help mothers whose milk supply is low or who are having difficulties nursing, or to help undernourished, mal-developed, or orphaned infants (Pimenteira Thomaz et al, 2008).…”
Section: Milk Donation and Motivationsmentioning
confidence: 99%
“…Additionally, the research suggests that several motivations to donate are likely unique to the context of donations to nonprofit milk banks. For example, motivations to donate include having a surplus of milk and wanting to avoid waste (e.g., Azema and Callahan, 2003;Osbaldiston and Mingle, 2007;O'Sullivan, Geraghty, and Rasmussen, 2016); anticipating reciprocity from others, in case the donor comes across the need in the future; a strong belief that human milk is the best nutrition option for babies; and feeling empathy and the desire to ease other babies' and mothers' suffering (Doshmangir, Naghshi, and Khabiri, 2019;Pimenteira Thomaz et al, 2008). Mothers' altruistic motivations are expressed in their desire to help mothers whose milk supply is low or who are having difficulties nursing, or to help undernourished, mal-developed, or orphaned infants (Pimenteira Thomaz et al, 2008).…”
Section: Milk Donation and Motivationsmentioning
confidence: 99%
“…Es imprescindible decir que el apoyo ofrecido por el BLH así como el apoyo de la familia 18 son esenciales para la manutención de esas mujeres como donantes tal y como ellas mismas citan (tabla 4). Una barrera importante a la donación es la falta de apoyo para la lactancia en el trabajo y por consiguiente para la donación, así como la reducción de la producción láctea que inicialmente les motivó a donasen.…”
Section: Enfermería Globalunclassified
“…1,[17][18][19][20] However, no studies were found that specifically relate to the donor's PCI for each reason to donate, making this present study the pioneer on this context.…”
Section: Discussionmentioning
confidence: 99%
“…11 The donors' profiles reflected what is described in the literature, characterized by young adults, married, employed and with different schooling levels. 10,20,21 The design of this profile is important, thus, these characteristics exert, albeit indirectly, a positive effect on the act of donating, contributing for a planning / strategies improvement to attract new donors.…”
Section: Discussionmentioning
confidence: 99%